Implementation and Hardware-In-The-Loop Simulation of a Magnetic Detumbling and Pointing Control Based on Three-Axis Magnetometer Data - Farissi, M. Salim; Carletta, Stefano; Nascetti, Augusto; Teofilatto, Paolo (Aerospace, 2019)
The subject of this work is the implementation and experimental testing of a purely magnetic attitude control strategy, which can provide stabilization after the deployment and pointing of the spacecraft without any attitude information. In particular, the control produces the detumbling of the satellite and leads it to a desired attitude with respect to the direction of the Earth magnetic field, based on the only information provided by a three-axis magnetometer. The system is meant to be used as a backup solution, in case of failure of the primary strategy and is designed considering the constraints set on time of operations, power consumption, and peak electric current for a typical CubeSat mission. The detumbling and pointing algorithms are implemented on the FPGA core of a CubeSat on-board computer and tested by Hardware-in-the-loop simulations. The simulation setup includes a Helmholtz cage, recreating the magnetic environment along the orbit, the on-board computer, a MEMS three-axis magnetometer and Simulink software, on which the attitude dynamics is propagated. Test on the real system can provide useful information to select the parameters of the control, such as the gains, to estimate the limits of the system, the time of operations and prevent failures.